Kategoria obecności w teatrze i performansie ostatniego półwiecza - Plata, Tomasz (My University, 2012)
Kategoria obecności jest jednym z podstawowych pojęć w najnowszej historii teatru i performance art. Namysł nad nią widać zarówno w pokoleniu kontrkultury lat 60., jak i w późniejszym pokoleniu twórców postmodernistycznych. Dlatego w pracy przedstawiona zostaje analiza dokonań przedstawicieli owych dwóch generacji: z jednej strony Jerzego Grotowskiego, z drugiej – nowojorskiego zespołu The Wooster Group. Grotowski zostaje ukazany w sposób odległy od dotychczasowych interpretacji: mówi się tu o pewnej archaiczności odczytań budowanych wokół kategorii aktu całkowitego, podróży do prawdziwej cząstki ludzkiej obecności. Analogicznie również w oglądzie The Wooster Group przekracza się interpretacyjną normę: o ile we wcześniejszych rozpoznaniach Wooster było prezentowane jako słownikowy teatr postmodernistyczny, a więc podważający wiarę w możliwość prostej ekspresji ludzkiej obecności na scenie, o tyle w „Kategorii obecności i nieobecności…” sugerowana jest myśl, że żaden teatr przed kategorią obecności uciec nie może, a Wooster świadomie zdaje z tego sprawę w swoich spektaklach.

The category of presence is one of the fundamental concepts which accounts for a major part of both practice and theory in the most recent history of theatre and performance art. Reflection on the category of presence can be witnessed in both the counterculture theatre of the 60’s and during the later generation of post-modern authors. For that reason the thesis presents a complex analysis of works by the central representatives of the aforementioned generations: Jerzy Grotowski on one side and The Wooster Group on the other. Jerzy Grotowski is presented in a manner markedly more remote from prior interpretations: the archaism of former interpretations built around the category of the absolute act and journey to the truth of human identity and presence is discussed. Correspondingly, in the study of The Wooster Group the prior interpretative norm is exceeded; in former research The Wooster Group was presented as an exact post-modern theatre, meaning a theatre that questions the faith in the possibility of simple expression of human presence on stage; interested more in disunion and the discontinuity of our identity, but in “Category of presence and absence…” it is suggested that no theatre can escape from the category of presence and all have to embrace it as an ally; something which The Wooster Group consciously shows in their plays.
The category of presence in theatre and performance during the last half-century
Wydział Nauk Społecznych: Instytut Kulturoznawstwa
Keywords: Teoria teatru; Theatre theory; Performans; Performance; Obecność; Presence; Dekonstrukcja; Deconstruction